2006
DOI: 10.1091/mbc.e06-06-0501
|View full text |Cite
|
Sign up to set email alerts
|

Akt Down-Regulates ERK1/2 Nuclear Localization and Angiotensin II-induced Cell Proliferation through PEA-15

Abstract: Angiotensin II (AngII) type 1 receptors (AT1) regulate cell growth through the extracellular signal-regulated kinase (ERK)1/2 and phosphatidylinositol 3-kinase (PI3K) pathways. ERK1/2 and Akt/protein kinase B, downstream of PI3K, are independently activated but both required for mediating AngII-induced proliferation when expressed at endogenous levels. We investigate the effect of an increase in the expression of wild-type Akt1 by using Chinese hamster ovary (CHO)-AT1 cells. Unexpectedly, Akt overexpression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Indeed, cross-talk between the PI3K/Akt and ERK pathways has been demonstrated in a diverse set of experimental conditions and in different cell types (41). Functional interactions between these two pathways could play a major role in regulating cell proliferation under particular conditions (42). Our data suggest that both PI3K and ERK antagonists could abrogate the activation of PI3K and ERK by balloon injury, consistent with overexpression of Klf4.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, cross-talk between the PI3K/Akt and ERK pathways has been demonstrated in a diverse set of experimental conditions and in different cell types (41). Functional interactions between these two pathways could play a major role in regulating cell proliferation under particular conditions (42). Our data suggest that both PI3K and ERK antagonists could abrogate the activation of PI3K and ERK by balloon injury, consistent with overexpression of Klf4.…”
Section: Discussionsupporting
confidence: 67%
“…The outcomes of signaling via the mitogen-activated protein kinase pathway are determined by the regulation of ERK nuclear translocation (5,10,44), which is required for activation of many transcription factors. The duration and extent of translocation is dependent on the type of stimulus, and ERK nuclear translocation is required to induce specific responses in the form of gene expression (45).…”
Section: Discussionmentioning
confidence: 99%
“…MEK binds to inactive ERK in resting cells (8). The natural regulation of ERK translocation has also been demonstrated by differential expression of cytoplasmic anchors such as PEA15 (9,10) or Sef (11) or expression of nuclear anchors such as DUSP5 (12) or Vanishing (13). It has been shown that the stimulation-induced nuclear accumulation of ERK requires the synthesis of short lived nuclear anchors (14).…”
mentioning
confidence: 99%
“…Nevertheless, PEA15 seems to be an excellent convergence point for ERK1/2 and Akt signaling pathways that needs to be fully addressed. This fact is even more interesting if we consider the implication of PEA15 in biological processes such as response to angiotensin (25) or cell motility and invasion (30,31). But the interference of E1a with the ERK1/2 signaling pathway is also due to the up-regulation of the FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…The stability and functionality of the protein seem to be dependent on the phosphorylation at two critical residues, Ser 104 and Ser 116 (24). This last residue, Ser 116 , is a natural phosphoacceptor of Akt activity with implications in the stability and functionality of the protein (25,26). Considering the inhibitory effect of E1a in the Akt signaling pathway (11,12), we decided to evaluate if E1a was affecting PEA15 stability through interference with Akt.…”
Section: E1a Blocks V-h-ras-induced Erk1/2 Activation and Promotes Itmentioning
confidence: 99%